2020
DOI: 10.3390/toxins12080509
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne Botulism: Clinical Diagnosis and Medical Treatment

Abstract: Botulinum neurotoxins (BoNTs) produced by Clostridia species are the most potent identified natural toxins. Classically, the toxic neurological syndrome is characterized by an (afebrile) acute symmetric descending flaccid paralysis. The most know typical clinical syndrome of botulism refers to the foodborne form. All different forms are characterized by the same symptoms, caused by toxin-induced neuromuscular paralysis. The diagnosis of botulism is essentially clinical, as well as the decision to apply the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 60 publications
0
38
0
16
Order By: Relevance
“…It probably shows a similar pattern than in experimental animals, notably supporting the long persistence of BoNT in the serum of certain patients. BoNT detection in serum is the most direct way to confirm a diagnosis of botulism [ 41 , 42 , 191 ]. However, the presence of BoNT in the blood circulation depends on the time between serum sampling and the symptom onset, the initial amount of toxin involved in the disease, which has been ingested or produced locally, and probably of individual host factors related to toxin absorption and/or elimination which remain to be defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It probably shows a similar pattern than in experimental animals, notably supporting the long persistence of BoNT in the serum of certain patients. BoNT detection in serum is the most direct way to confirm a diagnosis of botulism [ 41 , 42 , 191 ]. However, the presence of BoNT in the blood circulation depends on the time between serum sampling and the symptom onset, the initial amount of toxin involved in the disease, which has been ingested or produced locally, and probably of individual host factors related to toxin absorption and/or elimination which remain to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…BoNT amino acid sequences deduced from bont gene sequencing revealed that each toxinotype is subdivided into an increasing number of subtypes defined as >2.6% amino acid variation. Thus, 41 BoNT subtypes and multiple variants have been reported [5][6][7]. More recently, genome comparison showed the presence of bont related sequences in a few non-clostridial strains such as bont/Wo or bont/I from Weisenella oryzae, a bacterium of fermented rice, bont/J (ebont/F or bont/En) from an Enterococcus faecalis strain in a cow, and Cp1 from Chryseobacterium piperi from sediment [1,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clostridium botulinum , an anaerobic, rod-shaped bacterium, produces a neurotoxin called botulinum toxin (BoNT) during sporulation [ 1 , 2 , 3 ]. BoNT is the most potent biological toxin, as it causes botulism manifested by paralysis of muscles and eventual fatal respiratory failure [ 4 , 5 ]. When an action potential arrives at the cholinergic presynaptic nerve terminal, there is an influx of calcium into the presynaptic terminal, which then facilitates acetylcholine vesicle fusion with the presynaptic membrane; this fusion is facilitated by a group of proteins referred to as SNARE (soluble N-ethylmaleimide-sensitive factor attachment receptor) proteins, which include SNAP 25 (25 kD synaptosomal-associated protein) and Syntaxin [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four distinct phenotypic groups (I-IV) of C. botulinum are recognized. C. botulinum Groups I and II are primarily responsible for human botulism, the most frequent form of botulism in the European Union [5]. C. botulinum Group I has minimum and optimum growth temperatures of 12 • C and 37 • C, respectively.…”
Section: Introductionmentioning
confidence: 99%